Development of Konseling-Ku.id website to improve Islamic guidance and counseling services - Widyarto, Wikan Galuh; Pohan, Rizky Andana; Soleha, Irfana (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2024)
In the current era of the industrial revolution 4.0, digital technology-based innovations are urgently needed and are growing rapidly. The development method in this study is the Borg and Gall development model. The researcher made a development in the form of a website media named